2018
DOI: 10.1016/j.econedurev.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile crime and the four-day school week

Abstract: Little is known regarding the extent to which school changes youth criminal behavior in the short-term, if at all, and even less in known on this issue in rural areas. We leverage a unique policy, the adoption of the four-day school week across rural counties and years in Colorado, a school schedule that is becoming more common nationwide especially in rural areas, to examine the causal link between school and youth crime. Those affected by the policy spend the same number of hours in school each week as stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Further quasi-experimental research that considers the effects of the 4-day school week on other student and community outcomes is recent and sparse: The entirety consists of two working papers examining housing prices (Nowak et al, 2019) and parental labor supply (Ward, 2019) and one peer-reviewed publication examining delinquency (Fischer & Argyle, 2018). Based on Colorado housing transaction data from the first urban district to ever adopt a 4-day school week, Nowak et al (2019) find a 2% to 5% decrease in house prices relative to surrounding school districts as an effect of 4-day school week adoption.…”
Section: Other Effects Of the 4-day School Weekmentioning
confidence: 99%
See 1 more Smart Citation
“…Further quasi-experimental research that considers the effects of the 4-day school week on other student and community outcomes is recent and sparse: The entirety consists of two working papers examining housing prices (Nowak et al, 2019) and parental labor supply (Ward, 2019) and one peer-reviewed publication examining delinquency (Fischer & Argyle, 2018). Based on Colorado housing transaction data from the first urban district to ever adopt a 4-day school week, Nowak et al (2019) find a 2% to 5% decrease in house prices relative to surrounding school districts as an effect of 4-day school week adoption.…”
Section: Other Effects Of the 4-day School Weekmentioning
confidence: 99%
“…Fischer and Argyle’s (2018) quasi-experimental study exploits variation in the adoption of the 4-day school week across rural schools in Colorado to examine the relationship between school attendance and juvenile crime. They find that on Fridays, the day off for 4-day schools, the corresponding police and sheriff agencies where at least one 4-day high school was located experienced a 20% increase in overall crime and a 27% increase in property crime among juveniles compared to the agencies in areas composed of high schools with 5-day weeks.…”
Section: Other Effects Of the 4-day School Weekmentioning
confidence: 99%
“…7 In contrast, a Colorado study of community-level crime found juvenile crime increased in communities that adopted a 4-day schedule. 8 Other studies have found associations between school days without classes, such as teacher in-service days and strike days, and increased property crime rates. 9,10 These studies limited their investigation to crime rates and did not explore health outcomes or other adolescent risk behaviors.…”
mentioning
confidence: 98%
“…Currently, 1,500 schools in approximately 600 school districts across at least 24 states operate on a four-day school week schedule (Thompson, et al, 2019) Despite the growing use of these school schedules nationwide, little causal evidence exists on the effects of these policies on school, community, and student outcomes. To date, a handful of studies have conducted quasi-experimental analyses of the unintended effects of four-day school weeks on student achievement (Anderson and Walker, 2015; Thompson, 2019), juvenile crime (Fischer and Argyle, 2018), and maternal labor supply (Ward, 2019), but this is the first study to causally examine the direct effects 1 While these approaches have helped these school districts become more financially viable, many of these -increasing class sizes (e.g., Krueger, 1999), closing schools (e.g., Engberg, et al, 2012), and financial intervention systems (e.g., Thompson, 2016) in particular -have been found to negatively impact student achievement. of four-day school weeks on cost savings.…”
Section: Introductionmentioning
confidence: 99%